2016
DOI: 10.1097/md.0000000000005142
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory syncytial virus a and b display different temporal patterns in a 4-year prospective cross-sectional study among children with acute respiratory infection in a tropical city

Abstract: Respiratory syncytial virus (RSV) is one of the most common etiological agents of childhood respiratory infections globally. Information on seasonality of different antigenic groups is scarce. We aimed to describe the frequency, seasonality, and age of children infected by RSV antigenic groups A (RSVA) and B (RSVB) among children with ARI in a 4-year period.Children (6–23 months old) with respiratory infection for ≤7 days were enrolled in a prospective cross-sectional study, from September, 2009 to October, 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 26 publications
1
9
1
1
Order By: Relevance
“…Even with a cutoff of >40% genome coverage, we identi ed RSV in 79% (although most RSV infections in children are thought to be symptomatic) and CoVs in 47% of HC samples ( Supplementary Table S1). Similarly, this study revealed a high frequency (56%) of RSV-A and RSV-B co-infections in RSV-ARI samples, while previous studies have shown RSV-A and RSV-B coinfections ranging from 0.1% to 0.4% of RSV-ARI 43,44 . The frequency of RSV coinfections was greater in the RSV severe group (69.6%) compared to RSV mild group (37.5%) (Figure 2b).…”
Section: Discussionsupporting
confidence: 72%
“…Even with a cutoff of >40% genome coverage, we identi ed RSV in 79% (although most RSV infections in children are thought to be symptomatic) and CoVs in 47% of HC samples ( Supplementary Table S1). Similarly, this study revealed a high frequency (56%) of RSV-A and RSV-B co-infections in RSV-ARI samples, while previous studies have shown RSV-A and RSV-B coinfections ranging from 0.1% to 0.4% of RSV-ARI 43,44 . The frequency of RSV coinfections was greater in the RSV severe group (69.6%) compared to RSV mild group (37.5%) (Figure 2b).…”
Section: Discussionsupporting
confidence: 72%
“…RSV detection was significantly lower at only 2.3% of tested patients compared to previously published reports of 30-40% in other developing countries where the bulk of the children were seen in hospitals or emergency rooms (McCracken et al, 2013;Dawood et al, 2015;Bouzas et al, 2016). This low level of detection may have been due to initial storage of nasal swabs at À20 C which has been found to decrease RSV detection (Nunes and Moura, 2006) and our patients being 3-20 years old when the highest rate of the RSV positivity are typically among children 2 years of age.…”
Section: Discussioncontrasting
confidence: 70%
“…On the other hand, Caini et al demonstrated that influenza cases peaked between June and September (dry season), in countries of the Southern hemisphere, including south and southeast Brazil. Regarding the seasonality of RSV, Bouzas et al analyzed the incidence of RSV associated with seasonal distribution in the city of Salvador, Brazil. They observed the prevalence of RSV group A genotype in the dry seasons and, on the other hand, the higher incidence RSV group B genotype in the rainy season.…”
Section: Discussionmentioning
confidence: 99%